An exploratory study investigating the effect of targeted hyperoxemia in a randomized controlled trial in a long-term resuscitated model of combined acute subdural hematoma and hemorrhagic shock in cardiovascular healthy pigs - Datzmann, Thomas; Münz, Franziska; Hoffmann, Andrea; Moehrke, Elena; Binzenhöfer, Martha; Gröger, Michael; Kapapa, Thomas; Mathieu, René; Mayer, Simon; Zink, Fabian; Gässler, Holger; Wolfschmitt, Eva-Maria; et al. (Frontiers in Immunology, 2023)
Severe physical injuries and associated traumatic brain injury and/or hemorrhagic shock (HS) remain a leading cause of death worldwide, being aggravated by accompanying extensive inflammation. Retrospective clinical data indicated an association between mild hyperoxemia and improved survival and outcome. However, corresponding prospective clinical data including long-term resuscitation merely exist. Therefore, the present study explored the effect of mild hyperoxemia for 24 hours in a prospective, randomized controlled trial in a long-term resuscitated model of combined acute subdural hematoma (ASDH) and HS. ASDH was induced by injecting 0.1 ml/kg autologous blood into the subdural space with HS being triggered by passive removal of blood. After 2 hours, the animals received full resuscitation, including retransfusion of the shed blood and vasopressor support. During the first 24 hours, the animals underwent either targeted hyperoxemia (PaO2 = 200 – 250 mmHg) or normoxemia (PaO2 = 80 – 120 mmHg) with a total observation period of 55 hours after the initiation of ASDH and HS. Survival, cardiocirculatory stability, and demand for vasopressor support was comparable between both groups. Likewise, humoral markers of brain injury and systemic inflammation were similar. Multimodal brain monitoring, including microdialysis and partial pressure of O2 in brain tissue, showed no significant differences either, despite a significantly better outcome regarding the modified Glasgow Coma Scale 24 hours after shock favoring hyperoxemia. In summary, the present study reports no deleterious and few beneficial effects of mild targeted hyperoxemia in a clinically relevant model of ASDH and HS with long-term resuscitation in otherwise healthy pigs. Further beneficial effects on neurological function were most likely missed due to the high mortality in both experimental groups. The present study remains exploratory due to the unavailability of an a priori power calculation resulting from the lack of needed data.